Формування технологічної культури майбутнього викладача математики - Адаменко, О. О. (НТУ "ХПІ", 2015)
У статті аналізуються особливості формування технологічної культури майбутнього викладача математики. Автором розкрито зміст технологій евристичного навчання математики, хмарних технологій та проектних технологій, що сприяють підготовці майбутніх викладачів математики.

The article deals with peculiarities in formation of technological culture of a future teacher of mathematics. The author reveals the content of technologies of heuristic teaching of mathematics, cloud technologies and project technologies that promote the training of future teachers of mathematics.
Formation of tehnological culture of a future teacher of mathematics
Keywords: математична культура; технологія евристичного навчання; хмарна технологія; проектна технологія; technological culture; mathematical culture; heuristic teaching technology; cloud technology; project technology